Annual report RUAF - Cities farming for the future, South and SOUTHEAST ASIA Region, 2008 - Amerasinghe, Priyanie H.; Ishaq, S.; Radar, V. (International Water Management Institute, 2009)
This report documents the fourth year and final report of the RUAF-CFF programme in the South and SOUTHEAST ASIA region, coordinated by the International Water Management Institute, Hyderabad office, India. It is arranged in three sections: Introduction, activities for the year 2008 and cumulative results of 2005 -2008. The overall content reflects the activates, outcomes and outputs of the four year RAFT-CFF programme.